Pelaksanaan Penerbitan Sertifikat Pengganti di Kantor Pertanahan Wilayah Kabupaten Kotawaringin Barat - Alifa Putri Rahmadhani (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Protecting the rights, rights and interests of the people has an important role of the government. To prevent the increasing number and development of land conflicts in the community, it is very necessary to make sure solutions, for example, in order to meet the needs of the community which are usually used for housing, livelihoods, and daily needs, it should provide legal protection for land rights, and especially land ownership rights that are widely owned by the community. From the description above, the certificate of ownership of land is very important to maintain its existence, but until now there are still applications for replacement certificates because they are lost and damaged, so the author is interested in studying more deeply about the responsibility of the BPN in the West Kotawaringin Regency area for the issuance of replacement certificates. The author uses this type of empirical legal research. The data analysis technique is carried out in a descriptive, qualitative manner, namely by giving a detailed and in-depth presentation and explanation and for data collection by looking for data and information in relevant locations related to the research topic by interviews, library studies, and the internet.